1984
DOI: 10.1021/jf00125a067
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of controlled-release formulations of 2,6-dichlorobenzonitrile

Abstract: The herbicide dichlobenil (2,6-dichlorobenzonitrile) was incorporated in alginate-and carboxymethylcellulose (CMC)-based granules to obtain controlled-release (CR) properties. The effects of the addition of kaolin, an inexpensive filler, on release rate and granule yield were studied. Yield was increased more than 13-fold by the addition of 20% kaolin to the formulation. Release profiles were constructed for the release of dichlobenil from conventional (23-day release) and CR granules (> 150-day release for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 5 publications
(5 reference statements)
0
20
0
Order By: Relevance
“…These soil particles occupied the granular surface and reduced the release rate of imidacloprid into paddy water as a result of previous findings. 3,10,17,25,26) Again, the covered soil particles play a role, as does the controlled release layer discussed previously. 24,27) This layer partly reduced the imidacloprid release rate in both treatments.…”
Section: Pesticide Behavior In Paddy Water and Paddy Surface Soilmentioning
confidence: 83%
See 2 more Smart Citations
“…These soil particles occupied the granular surface and reduced the release rate of imidacloprid into paddy water as a result of previous findings. 3,10,17,25,26) Again, the covered soil particles play a role, as does the controlled release layer discussed previously. 24,27) This layer partly reduced the imidacloprid release rate in both treatments.…”
Section: Pesticide Behavior In Paddy Water and Paddy Surface Soilmentioning
confidence: 83%
“…Soil particles covered the granule insecticide retarded diffusion process of pesticide to the aqueous phase. 3,10,17,25,26) Moreover, previous studies reported that soil particles may behave like a controlled release formulation because of their adsorption-desorption characteristics. 24,27) In addition to the controlled release formulation, this soil layer promoted a slower release rate in AS treatment; consequently, the low concentration of imidacloprid was found in AS treatment.…”
Section: Pesticide Behavior In Paddy Water and Paddy Surface Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been regarded as an excellent polysaccharide for drug delivery system due to its good properties such as nontoxicity, immunogenicity, biocompatibility and biodegradability [14][15][16][17]. However, pure alginate has its inherent drawbacks such as poor mechanical strength, uncontrolled degradation and extensive water uptake properties [18,19], which restrict its real applications [20]. It has been reported that amphiphilic alginate derivative modified by introducing the hydrophobic groups into the hydrophilic polysaccharide is not only a good candidate for the formation of nanoparticles, but also an effective way to enhance its affinity to the hydrophobic drug [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Alginates have been used as matrices for controlled release of pesticides by several workers. Connick et al 3 described a series of alginate–kaolin‐based 2,6‐dichlorobenzonitrile CR formulations 3. In aquatic release experiments, the authors reported that the release of active ingredient became slower as the kaolin concentration was increased.…”
Section: Introductionmentioning
confidence: 99%